1998
DOI: 10.1038/sj.bmt.1701341
|View full text |Cite
|
Sign up to set email alerts
|

Successful double autografts for patients with relapsed clear cell sarcoma of the kidney

Abstract: Summary:Although the prognosis of clear cell sarcoma of the kidney (CCSK) has improved, when metastases occur the probability of cure is very low. We have treated two pediatric patients with relapsed CCSK, one with multiple bone metastases and another with brain metastases. After one or two courses of re-induction chemotherapy and radiation therapy to the sites of metastasis, they received double high-dose chemotherapy with autologous bone marrow rescue. Conditioning regimens were ifosphamide plus melphalan fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Intensive treatment, including chemotherapy as well as achieving local control by complete surgery (where possible) and/or radiotherapy, seems to enhance consolidation of second CR. Summarising our study and previous reports, in total 24 relapsed CCSK patients received high-dose chemotherapy followed by ABMT, of which 12 patients (50%) were alive without disease after a median follow-up of 52 months (range, 9–103 months) (Kullendorff and Bekassy, 1997; Pein et al , 1998; Yumura-Yagi et al , 1998; Radulescu et al , 2008; Furtwängler et al , 2013). This seems to be promising, although it should be emphasised that this high-dose chemotherapy is mostly applied in a selected group of patients who already achieved a second CR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Intensive treatment, including chemotherapy as well as achieving local control by complete surgery (where possible) and/or radiotherapy, seems to enhance consolidation of second CR. Summarising our study and previous reports, in total 24 relapsed CCSK patients received high-dose chemotherapy followed by ABMT, of which 12 patients (50%) were alive without disease after a median follow-up of 52 months (range, 9–103 months) (Kullendorff and Bekassy, 1997; Pein et al , 1998; Yumura-Yagi et al , 1998; Radulescu et al , 2008; Furtwängler et al , 2013). This seems to be promising, although it should be emphasised that this high-dose chemotherapy is mostly applied in a selected group of patients who already achieved a second CR.…”
Section: Discussionsupporting
confidence: 82%
“…Up until now, only three descriptive reports on clinical characteristics, treatment and outcome of relapsed CCSK have been published, including 11 patients in total (Table 1) (Kusumakumary et al , 1997; Yumura-Yagi et al , 1998; Radulescu et al , 2008). Therefore, data on clinical features of these patients are scarce and the contribution of chemotherapy, surgery, radiotherapy and high-dose chemotherapy followed by ABMT to optimal treatment of relapsed CCSK has not been established as yet.…”
mentioning
confidence: 99%
“…Furthermore, treatment with high-dose chemotherapy (extremely high, potentially toxic doses of chemo therapy) followed by autologous stem cell transplantation (HD-ASCT) to consolidate the second complete remission seems to be of value 21,55 . In total, the outcomes of 24 patients with CCSK who experienced relapse and received HD-ASCT have been reported in the literature, of whom 50% were alive without disease after a median follow-up duration of 52 months, whereas the average 5-year OS of patients with relapsed CCSK is about 26% 21,[55][56][57][58] . Importantly, this HD-ASCT treatment was mostly given to a selected group of patients with relapsed disease who already achieved second complete remission; thus, the positive effect of HD-ASCT might (in part) be attributable to this selection of patients.…”
Section: Treatment Recommendations For Relapsed Diseasementioning
confidence: 99%
“…Jung et al in a study of 60 temporal bones with metastatic disease, found involvement of the facial nerve in 14 (23%) [105]. One study pointed out that only 50% of patients with tumoral invasion of the facial canal clinically had some degree of facial paralysis, although virtually all patients with tumor extension beyond the epineural sheath had complete paralysis [99].…”
Section: Temporal Bone Syndromementioning
confidence: 99%
“…The authors suggest that ICE chemotherapy, together with radiation therapy and surgery, provided a reasonable salvage treatment regimen for recurrent CCSK that has metastasized to the brain [102]. The role of high dosechemotherapy remains undefined, despite several encouraging reports [103][104][105].…”
Section: Clear Cell Sarcoma Of the Kidney (Ccsk)mentioning
confidence: 99%